Therapeutic Effects of Berberine Hydrochloride on Stress-Induced Diarrhea-Predominant Irritable Bowel Syndrome Rats by Inhibiting Neurotransmission in Colonic Smooth Muscle - Lu, Yulin; Huang, Jingjing; Zhang, Yao; Huang, Zitong; Yan, Weiming; Zhou, Tianran; Wang, Zhesheng; Liao, Lu; Cao, Hongying; Tan, Bo (Frontiers in Pharmacology, 2021)
The etiology of diarrhea-predominant irritable bowel syndrome (IBS-D) is complicated, and closely related to the neurotransmission in the gastrointestinal (GI) tract. A major challenge for IBS-D research is to develop new strategies for treating this disease. Berberine hydrochloride (BBH), the derivative of berberine, is an herbal constituent used to treat irritable bowel syndrome. Previous studies have shown that BBH has potential anti-inflammatory, antibacterial, analgesic, and antidiarrheal effects and a wide range of biological activities, especially in regulating the release of some neurotransmitters. A modified IBS-D rat model induced by chronic restrain stress was used in all experiments to study the effects of BBH on the GI tract. This study determined the measurement of abdominal wall reflex (AWR) response to graded colorectal distention (CRD; 20, 40, 60, and 80 mmHg) and observed the fecal areas of the stress-induced IBS-D model. Experiments were conducted using organ bath techniques, which were performed in vitro using strips of colonic longitudinal smooth muscle. Inhibitory and excitatory neurotransmitter agents were added to each organ bath to observe contractile responses on the strips and the treatment effect exerted by BBH. The IBS-D rat model was successfully induced by chronic restraint stress, which resulted in an increased defecation frequency and visceral hypersensitivity similar to that of humans. BBH could reduce 4-h fecal areas and AWR response to CRD in IBS-D. The stress-induced IBS-D model showed upregulated colonic mRNA expression levels of 5-hydroxytryptamine-3A receptor and downregulated expression levels of neuronal nitric oxide synthase. Meanwhile, BBH could reverse this outcome. What the contractile response caused by substances able to modulate neurotransmission involved in IBS-D, including the agonist of acetylcholine, carbachol; NOS inhibitor, L-NAME; and P2Y1 receptor antagonist, MRS2500, in the colonic longitudinal smooth muscle can be inhibited by BBH. In summary, BBH promotes defecation frequency and visceral hypersensitivity in IBS-D and exerts inhibitory effects on contractile responses in colonic longitudinal smooth muscle. Thus, BBH may represent a new therapeutic approach for treating IBS-D.